2020
DOI: 10.1016/j.sjbs.2020.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Antibiogram and phylogenetic diversity of enterotoxigenic Staphylococcus aureus strains from milk products and public health implications

Abstract: Food poisoning caused by Staphylococcus aureus ( S. aureus ) toxins is considered one of the foremost public health threat that usually occurs through the ingestion of raw milk contaminated with staphylococcal enterotoxins. The current study spotlights on the prevalence, antibiogram and genetic diversity of S. aureus enterotoxin genes. One hundred and fifty of raw milk (90) and ice cream (60) samples were randomly collected from local markets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 44 publications
(40 reference statements)
3
21
0
Order By: Relevance
“…Several Egyptian and global studies performed the comparative sequence analysis of S. aureus isolated from bovine subclinical mastitis and various food sources [16,[51][52][53]. A previous study employing the 16S rRNA genes sequencing and microarray analysis revealed six clonal complexes of S. aureus recovered from household cattle and buffaloes in Egypt [54].…”
Section: Discussionmentioning
confidence: 99%
“…Several Egyptian and global studies performed the comparative sequence analysis of S. aureus isolated from bovine subclinical mastitis and various food sources [16,[51][52][53]. A previous study employing the 16S rRNA genes sequencing and microarray analysis revealed six clonal complexes of S. aureus recovered from household cattle and buffaloes in Egypt [54].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were obtained by Mohammed and Hafez [ 33 ] in Egypt, who detected high resistance against chloramphenicol and ampicillin (100%), streptomycin (66.6%), gentamicin and trimethoprim-sulphamethoxazole (33.3%), and erythromycin (16.6%). In a recent study in Egypt, S. aureus demonstrated extreme resistance to cefoxitin, penicillin, cephradine, tetracycline, trimethoprim-sulphamethoxazole, and norfloxacin in samples from raw milk and ice cream [ 4 ]. In China, Wu and colleagues [ 32 ] also recorded high resistance of S. aureus isolated from retail meat and meat products against penicillin (84.6%), ampicillin (85.4%), erythromycin (52.7%), tetracycline (49.3%), kanamycin (45.3%), telithromycin (30.1%), clindamycin (29.6%), streptomycin (21.1%), norfloxacin (20.4%), gentamicin (19.4%), fusidic acid (18.4%), and ciprofloxacin (16.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Globally, S. aureus causes widely distributed opportunistic, nosocomial, and population-related diseases [ 3 ]. A recent report stated that S. aureus strains can spread to different geographical regions through food and milk products [ 4 ]. According to a surveillance study in India, a lack of hygienic procedures during processing and post-processing handling of food products, particularly those of animal origins such as eggs, meat, and milk, facilitated microbial contamination [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study was conducted in Egypt and confirmed the existence of the nuc gene in all S. aureus strains [45,46]. This contrasts with the results published by Abdeen et al [47] who found that approximately 70% of S. aureus isolates carried the nuc gene.…”
Section: Resultsmentioning
confidence: 87%